Boys”‘Stones, G., El Murr, D. and Gill, C. (eds.). (2013). The Platonic Art of Philosophy. Cambridge, Cambridge University Press - Pitteloud, Luca Jean (Revista Archai, 2016)
Compte”‘rendu: Boys”‘Stones, G., El Murr, D. and Gill, C. (eds.). (2013). The Platonic Art of Philosophy. Cambridge, Cambridge University Press